STUDY OF INFLUENCE OF FLOCCULANT DOSE ON SEDIMENTATION PROCESS AT DEWATERING PLANT PT. FREEPORT INDONESIA - OKTAVIANUS BUTARBUTAR (NIM. 125 08 027), IMMANUEL
Dewatering Plant (DWP) is one of the process units owned by PT Freeport Indonesia (PTFI), which is located on the island of Amamapare. DWP-PTFI serves as a drying unit before concentrates are shipped and marketed. DWP-PTFI consists of one unit of Vertical Pressure Air (VPA), 13 disc filter units and three units of rotary dryer. Filtrates resulted from VPA process or disc filters are not immediately discarded because they contain a lot of suspended solids. In order to precipitate suspended solids contained in the filtrate, three series of sedimentation stage were carried out in thickener, lamella thickener, and a settling pond. Sedimentation is a deposition process by utilizing gravity force with the aim of separating solids from water. Density difference between particles and water makes the particles move down and separated from the water. Particle size plays an important role in the process of sedimentation. If the particles are very fine, the precipitation will be difficult because grafity force of fine particles is lower than water buoyancy. Very fine particle must be aggregate into larger sizes. Flocculant is a reagent that serves to aggregate particles using the principle of "bridge". DWP-PTFI used flocculant in each unit of sedimentation. PTFI has plans to use Rheomax 1050 as a flocculant to replace the current flocculant used i.e Magnafloc 3230. To evaluate the performance of both flocculants, experiments were conducted in the laboratory and plant. In general, the experiments were divided into two groups, namely A and B experiment. Experiment A is aimed to compare the performance between Magnafloc 3230 and Rheomax 1050, whilst experiment B is aimed to find the optimum dose of Rheomax 1050 for lamella thickener and settling pond, respectively if Rheomax 1050 used as a flocculant in DWP-PTFI. The addition of coagulant in Experiment B become additional options to obtain better results. From the results of experiment A, it was shown that Rheomax 1050 can give better results than Magnafloc 3230. During laboratory testing and plant trial, it was shown that average turbidity of the overflow was lower when using Rheomax 1050, compared to Magnafloc 3230. In experiment B, it was found that optimum dose of Rheomax 1050 for lamella thickener and settling pond is 5 g / ton. When accompanied by the addition of coagulant, the optimum dose for the lamella thickener and settling pond respectively obtained at doses of 15 g / t flocculant with 20 g / t coagulant and 5 g / t flocculant with 20 g / t coagulant.